2010
DOI: 10.4314/sajas.v40i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whey and molasses as silage additives on potato hash silage quality and growth performance of lambs

Abstract: ________________________________________________________________________________ AbstractThe aim of the study was to determine the effect of whey or molasses on the fermentation quality when added to potato hash silage. In addition, lamb performance, digestibility and feed intake of diets containing potato hash silage were compared with a diet containing maize silage (MSd). Potato hash silage (treated with no additive, or whey, or molasses) and MS were produced in 210 L drums for 90 days and the fermentation q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…There was similar growth performance for the DO and R 1 lambs (197.6 g and 204.3 g, respectively) (P >0.05). These values were comparable with those recorded by Nkosi & Meeske (2010), who reported ADGs ranging between 190 g/day and 250 g/day. Average daily gain of F 1 crossbred lambs did not differ significantly (P >0.05) from that recorded in the purebred DO and TA (188.9 g/day,197.6 kg/day and 185.2 kg/day, respectively).…”
Section: Resultssupporting
confidence: 90%
“…There was similar growth performance for the DO and R 1 lambs (197.6 g and 204.3 g, respectively) (P >0.05). These values were comparable with those recorded by Nkosi & Meeske (2010), who reported ADGs ranging between 190 g/day and 250 g/day. Average daily gain of F 1 crossbred lambs did not differ significantly (P >0.05) from that recorded in the purebred DO and TA (188.9 g/day,197.6 kg/day and 185.2 kg/day, respectively).…”
Section: Resultssupporting
confidence: 90%
“…The results of this experiment showed that addition of whey and molasses had no significant effects on body weight, feed intake and FCR of Simmental fattening calves. Nkosi and Meeske (2010) reported that adding molasses on potato hash silage, improved fermentation and increased feed intake and body weight of growing lambs. Addition urea and molasses on Palm silage increased body weight and improved FCR of fattening goats (salemi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Sadri et al (2018) noticed that average daily gain (ADG) of growing lambs was increased with increasing potato-wheat straw silage in the rations up to 300 g/kg DM. Nkosi and Meeske (2010) found that ADG was 192 g/d of lambs fed ration containing 20% potato hash silage with CFM. Nkosi and Ratsaka (2010) found that feed conversion was 10.2 of lambs fed ration containing 22.5% silage of potato hash and hay + CFM.…”
Section: Introductionmentioning
confidence: 99%